2016
DOI: 10.1186/s13256-016-1128-8
|View full text |Cite
|
Sign up to set email alerts
|

Folie à Deux and its interaction with early life stress: a case report

Abstract: BackgroundFolie à deux is a very rare psychiatric syndrome in which a psychotic symptom is transmitted from one individual to another. We present a case of folie à deux occurring during childhood, which is not an usual presentation of this syndrome. In this case, the disorder is correlated with child abuse and neglect, which possibly had a role in the development of the symptoms in our case.Case presentationWe present a case of folie à deux between an “induced” 9-year-old black Brazilian boy and the “inducer”,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
10
0
3
Order By: Relevance
“…According to Lazurus, two preconditions must exist before folie à deux can develop: an intimate emotional association between the inducer and the affected person and a genetic predisposition to psychosis, such as blood relations with the primary patient [ 7 ]. Although debated, social isolation has also been considered a potential risk factor for shared psychosis in recent literature [ 2 , 8 ]. As of 2020, the existing literature on clinical, diagnostic, and therapeutic aspects of folie a deux describes 7 reported cases documented in the timeframe between 1995 and 2019, wherein social isolation was mentioned as a major risk factor, with a prevalence higher than 60% in the listed cases (Arnone et al, 2006; Silveira & Seeman, 1995) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Lazurus, two preconditions must exist before folie à deux can develop: an intimate emotional association between the inducer and the affected person and a genetic predisposition to psychosis, such as blood relations with the primary patient [ 7 ]. Although debated, social isolation has also been considered a potential risk factor for shared psychosis in recent literature [ 2 , 8 ]. As of 2020, the existing literature on clinical, diagnostic, and therapeutic aspects of folie a deux describes 7 reported cases documented in the timeframe between 1995 and 2019, wherein social isolation was mentioned as a major risk factor, with a prevalence higher than 60% in the listed cases (Arnone et al, 2006; Silveira & Seeman, 1995) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Case reports suggest childhood trauma as risk factors for the secondary (induced) patient. 12 Social isolation limiting environmental input and opportunities for reality testing is also common. 13,14 There is a similar prevalence of schizophrenia in families of both individuals in Folie à Deux.…”
Section: Discussionmentioning
confidence: 99%
“…The content of the shared delusional beliefs may depend on the diagnosis of the primary case and can include bizarre delusions, or nonbizarre delusions characteristic of delusional disorder, and delusions congruent with mood. 21 All kinds of delusional contents can be seen in this disorder. 22 However, persecutory, religious, and grandiose themes are the most common.…”
Section: Nosographic Questionsmentioning
confidence: 98%
“…[64][65][66][67][68][69][70][71] In addition, it has been reported that individuals who develop FaD have a high risk of schizophrenia in their families, with a very high prevalence of schizophrenia in firstdegree relatives (6.5%-26.2%), which is similar to the prevalence seen in first-degree relatives of schizophrenic patients (5.0%-16.9%). 21 Despite this evidence, the extent of genetic influence is difficult to determine. 26 Socioclinical substrates such as suggestibility and some cultural traits and religious beliefs could also provide the soil for the sharing of delusions.…”
Section: Risk and Etiological Factorsmentioning
confidence: 99%
See 1 more Smart Citation